2014
DOI: 10.1038/nchembio.1651
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic and extrinsic effects of N-linked glycans on glycoproteostasis

Abstract: Proteins that traffic through the eukaryotic secretory pathway are commonly modified with N-linked carbohydrates. These bulky amphipathic modifications at asparagines intrinsically enhance solubility and folding energetics through carbohydrate-protein interactions. N-linked glycans can also extrinsically enhance glycoprotein folding by utilizing the glycoprotein homeostasis or “glycoproteostasis” network, comprising numerous glycan binding and/or modification enzymes or proteins that synthesize, transfer, scul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(154 citation statements)
references
References 99 publications
(147 reference statements)
3
149
0
2
Order By: Relevance
“…Endogenous wildtype Chlamydomonas RbcL is acetylated at Pro-3 (Houtz et al, 1992), hydroxylated at Pro-104 and Pro-151, and methylated at Cys-256 and Cys-369 (Taylor et al, 2001), whereas none of these modifications have been reported in Synechococcus RbcL. However, among post-translational modifications, glycosylation is believed to be the most important modification for folding and stability of polypeptides (Hebert et al, 2014). Since glycosylation does not naturally occur in wild-type endogenous Chlamydomonas RbcL, the limited post-translational modification systems in E. coli may ultimately have less of an impact on the ability of the chimeric Rubiscos to fold heterologously.…”
Section: Discussionmentioning
confidence: 97%
“…Endogenous wildtype Chlamydomonas RbcL is acetylated at Pro-3 (Houtz et al, 1992), hydroxylated at Pro-104 and Pro-151, and methylated at Cys-256 and Cys-369 (Taylor et al, 2001), whereas none of these modifications have been reported in Synechococcus RbcL. However, among post-translational modifications, glycosylation is believed to be the most important modification for folding and stability of polypeptides (Hebert et al, 2014). Since glycosylation does not naturally occur in wild-type endogenous Chlamydomonas RbcL, the limited post-translational modification systems in E. coli may ultimately have less of an impact on the ability of the chimeric Rubiscos to fold heterologously.…”
Section: Discussionmentioning
confidence: 97%
“…Or is the observed essentiality of formation of the C-terminal disulfide favored by sequence-encoded folding information? ATIII appears to rely on the lectin chaperone system comprised of calnexin, calreticulin, as well as the UDP-glucose, glycoprotein glucosyltransferase 1, which directs rebinding and ER retention of nonnative substrates (31,32). The secretion level of ATIII was reduced by two-thirds in the absence of intervention by the lectin chaperone network; however, this diminished secreted fraction was active.…”
Section: Atiiimentioning
confidence: 95%
“…N-glycans are synthesized and transferred to polypeptides containing a signal peptide, by glycosyltransferase, at aspargine residues within the NxS/T sequon on the luminal side of the ER and Golgi (Molinari, 2007;Hebert et al, 2014). However, the mechanism by which HMGB1 becomes glycosylated despite being devoid of signal peptide is still is unknown, as Nglycosylation rarely exists in the cytosol.…”
Section: Discussionmentioning
confidence: 99%